Fourth Development Commissioners' Conference on Community Projects at Shimla (9th to 11th. May, 1955) Agenda-Notes on - Planning Commission (Planning Commission, 1955)
One would expect to find a careful and authoritative analysis of the impact of the programme in the Programme Evaluation Organization and National Sample Survey reports, when published. It appears, however, to those intimately connected with the operation of programme that it is playing a significant role in the social and economic transformation of the rural life of India. With the decision to cover by the end of the Second Five Year Plan the whole of rural India with National Extension Service and a substantial part of it under the Community Development plan, the programme has acquired a now significance in as much as the entire machinery of Government would have undergone by then a major change in emphasis from law and order and revenue collection towards the welfare of the people.
Community Projects Administration Government of India
Community Projects Administration Government of India